On Marginal Distributions of the Ordered Eigenvalues of Certain Random Matrices. (18th July 2010) - Zhang Zhang, Haochuan Haochuan; Jin Jin, Shi Shi; Zhang Zhang, Xin Xin; Yang Yang, Dacheng Dacheng
Abstract : This paper presents a general expression for the marginal distributions of the ordered eigenvalues of certain important random matrices. The expression, given in terms of matrix determinants, is compacter in representation and more efficient in computational complexity than existing results in the literature. As an illustrative application of the new result, we then analyze the performance of the multiple-input multiple-output singular value decomposition system. Analytical expressions for the average symbol error rate and the outage probability are derived, assuming the general double-scattering fading condition.